MEDICAL SUPPORT RESULT COMPLETENESS OF AN INFORMATION SYSTEM DESIGN FOR COVID-19 PATIENTS AFTER BEING HOSPITALIZED BASED ON VISUAL STUDIO 2010 - Aldi Rizki Irawan; Dina Sonia; Cahyadi Agustin; Santy Christinawati (LPSDI Bina Patria, 2022)
This study aims To explain the medical support result completeness of an information system design for covid-19 patients after being hospitalized The research method used is a descriptive method by conducting observations, interviews, and literature review. The software method used is the Waterfall development method. From the results of this study, the following problems were found: The process of recording the completeness of the information system for the results of medical support for Covid-19 patients still in manual method so that the recording gets to be less successful, the time wasteful in recording since it still employments the manual method, the difficulty in making a completeness report because the completeness of the medical support results are written randomly, the identity of the medical support result is often not in accordance with what is proposed. Therefore, the researchers designed an information system for the completeness of the results of medical support for covid-19 patients after being hospitalized using Microsoft Visual Studio 2010 to make it easier for officers to process the completeness of medical support results.